2013
DOI: 10.1111/mmi.12355
|View full text |Cite
|
Sign up to set email alerts
|

A conserved ClpP‐like protease involved in spore outgrowth in Bacillus subtilis

Abstract: Germination and outgrowth of endospores of the Gram-positive bacterium Bacillus subtilis involves the degradation and conversion to free amino acids of abundant proteins located in the spore core known as small acid-soluble proteins (SASP). This degradation is mediated primarily by the germination protease Gpr. Here we show that YmfB, a distant homolog of ClpP serine proteases that is highly conserved among endospore-forming bacteria, contributes to SASP degradation but that its function is normally masked by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…GPR was classified as an atypical aspartic acid protease (Carroll & Setlow, 2005) and recently the yyaC gene product, which belongs to the s F regulon of B. subtilis (Steil et al, 2005;Wang et al, 2006), was suggested as a putative GPR-like enzyme based on conserved aspartic acid residues similar to GPR (Carroll, 2008). However, enzyme activity and substrate specificity of GPR were analysed only in B. megaterium and B. subtilis (Sanchez-Salas et al, 1992;Carroll & Setlow, 2005;Traag et al, 2013). Our study confirms proteolytic activity of GPR (Cac1275) of C. acetobutylicum and for the first time, we believe, we demonstrate GPR-like activity for a YyaC homologue (Cac2857).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…GPR was classified as an atypical aspartic acid protease (Carroll & Setlow, 2005) and recently the yyaC gene product, which belongs to the s F regulon of B. subtilis (Steil et al, 2005;Wang et al, 2006), was suggested as a putative GPR-like enzyme based on conserved aspartic acid residues similar to GPR (Carroll, 2008). However, enzyme activity and substrate specificity of GPR were analysed only in B. megaterium and B. subtilis (Sanchez-Salas et al, 1992;Carroll & Setlow, 2005;Traag et al, 2013). Our study confirms proteolytic activity of GPR (Cac1275) of C. acetobutylicum and for the first time, we believe, we demonstrate GPR-like activity for a YyaC homologue (Cac2857).…”
Section: Discussionsupporting
confidence: 75%
“…A lower activity of YyaC might reflect the situation in B. subtilis (Sanchez-Salas et al, 1992;Traag et al, 2013). Moreover, different substrate specifities of GPR in Bacillus have been discussed as a result of environmental and conformational changes compared with the situation in vivo (Setlow, 1976(Setlow, , 1978.…”
Section: Discussionmentioning
confidence: 99%
“…The peptidase U32 protein YrrN is one member of the yrrMNO operon which is important for the biosynthesis of 5-hydroxyuridine, YrrN is involved in the synthesis of 5methoxyuridine (Nguyen et al 2011). The cytoplasmic ClpP-like germination protease TepA is involved in spore outgrowth in B. subtilis, and is not proposed to be a signal peptide peptidase but to degrade a specialized family of small DNA-binding proteins during the process of spore outgrowth (Traag et al 2013;Westers et al 2004a). YmfH is identi ed by the presence of Peptidase_M16 and Peptidase_M16_C domains, and is predicted to encode uncharacterized zinc protease with unknown speci city (Hummels et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The peptidase U32 protein YrrN is one member of the yrrMNO operon which is important for the biosynthesis of 5-hydroxyuridine, YrrN is involved in the synthesis of 5methoxyuridine (Nguyen et al 2011). The cytoplasmic ClpP-like germination protease TepA is involved in spore outgrowth in B. subtilis, and is not proposed to be a signal peptide peptidase but to degrade a specialized family of small DNA-binding proteins during the process of spore outgrowth (Traag et al 2013;Westers et al 2004a).YmfH is identi ed by the presence of Peptidase_M16 and Peptidase_M16_C domains, and is predicted to encode uncharacterized zinc protease with unknown speci city (Hummels et al 2017).In this study, the deletion of any of the four proteases improved the secretion of AiiO-AIO6, but the degree of improvement was different. Their effect on the secretion of AiiO-AIO6 in B. subtilis was YwpE > YrrN > TepA or YmfH, which may be due to the difference in the degradation ability of these proteases to AiiO-AIO6 or the degradation ability of the proteins assisting the secretion of AiiO-AIO6.…”
Section: Discussionmentioning
confidence: 99%